TO A QUESTION ABOUT THE MOTIVES OF DEPRIVATION GAMBLING RELIEF (on the example of the Republic of Tajikistan) - Tahmina Istamovna Sultonova (Вестник Северо-Кавказского федерального университета)
In this article the conclusion that the reasons for the deprivation requirements of the games and betting remedies are not associated with negative moments inherent in gambling, not to protect public morals, but only in their complete irrelevance to the state and society. We prove that the reason for the negative attitude to gambling by the state is only one factor to be associated with interest only to their members. Argued that in deciding whether to grant, in some cases the requirements of judicial protection of gambling and betting, fundamental to the legislator is not a social characteristic of gambling hobbies, and the role that they play in the economic circulation.